Modern educational technologies: psychology and pedagogy - Astafurova O. A., Kulagina I. I., Lavina T. A., Zakharova A. N., Gritsevich T. I., Grabar V. V., Lobanov S. V., Gordeev I. M., Ailarova Z. A., Kaloev T. V., Burukina O. A., Nikolina V. V., Aksenov S. I., Beliaeva T. K., Zulkharnaeva A. V., Loshchilova A. A., Fefelova O. E., Frolova S. V., Genvareva I. A., Marchenkova N. G., Sudakov D. V., Sudakov O. V., Sych G. V., Gordeeva O. I., Lastkov D. O., Klimenko A. I., Mikhailova T. V., Besedina E. I., Zhidkikh T. N., Obornev A. L., Gordova V. S., Stepanova T. N., Izranov V. A., Shutenko A. I., Ananeva M. A., Kharchenko I. E., Solnyshkina M. G., Katsero A. A., Kozlova I. V., Putilina S. I., Mosina N. A., Litvinchuk N. V., Belova E. G. (Modern educational technologies: psychology and pedagogy, 2023)
the chapter describes current trends in the digitalization of higher education. The pros, cons and prospects of digitalization of higher education in the technologically advanced era are considered. It offers pedagogical recommendations for the introduction and development of active digital learning, identifies barriers to its implementation and analyzes the necessary institutional actions to accelerate its implementation.
Keywords: высшее образование; образовательные технологии; higher education; цифровая трансформация; digital transformation; цифровое обучение; educational technologies; модели преподавания; teaching models; digital learning